Future of University in Conditions of Uncertainty and Complexity - G I. Lovetsky; P. V. Samylov; V. G. Kosushkin (Высшее образование в России)
The article focuses on the analysis of the role and place of the university in the concepts of restructuring the basic foundations of society on the principles of extensive use of information and communication technologies. It has been established that in the domestic system of training highly qualified personnel for the new economy, the contradictions between its elements are aggravated. On the one hand, universities have a high intellectual potential of teachers and scientists representing generations X and Y; they train the creative part of generation Z. An optimistic future scenario, as a product of university discussions, is presented in the mission of the university. On the other hand, the state and business community define the contours of the future in terms of simplicity, certainty, linear development, and high controllability. This approach is contrary to the global fundamental vectors that indicate the ability to work in conditions of complexity and uncertainty. The methodological basis of the study are systemic, constructivist and transdisciplinary approaches, applying the theoretical foundations of complex systems to social processes, and, above all, to the system of university education in Russia. The main conclusions are the following: 1) uncertainty and complexity of the future are not an obstacle to scenario forecasting in the sphere of higher education as a ground for the knowledge society; 2) this movement will be successful if the state and business community go to a higher level of strategic planning; 3) academically free university, humanistically oriented state reforms and programs of society modernization, socially oriented business (investments for a person) become the targets of the future. The results of the study can be used in the practice of Russian and international university education